2020
DOI: 10.1016/j.nbd.2019.104676
|View full text |Cite
|
Sign up to set email alerts
|

Ex vivo multi-electrode analysis reveals spatiotemporal dynamics of ictal behavior at the infiltrated margin of glioma

Abstract: The purpose of this study is to develop a platform in which the cellular and molecular underpinnings of chronic focal neocortical lesional epilepsy can be explored and use it to characterize seizure-like events (SLEs) in an ex vivo model of infiltrating high-grade glioma. Microelectrode arrays were used to study electrophysiologic changes in ex vivo acute brain slices from a PTEN/p53 deleted, PDGF-B driven mouse model of high-grade glioma. Electrode locations were co-registered to the underlying histology to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 48 publications
(68 reference statements)
3
8
0
Order By: Relevance
“…Moreover, this approach provided an electrophysiologic correlate for the GCaMP fluctuations observed in longitudinal in vivo imaging of this model 13 . In agreement with prior studies, our ex vivo acute tumor-bearing slices demonstrated increased excitability 4, 7, 12, 17, 42 and decreased FS cell firing 3 without significant increases in pyramidal cell activity. Additionally, peritumoral FS cell firing was less likely to be interictal, as it occurred predominantly within epileptiform bursts.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, this approach provided an electrophysiologic correlate for the GCaMP fluctuations observed in longitudinal in vivo imaging of this model 13 . In agreement with prior studies, our ex vivo acute tumor-bearing slices demonstrated increased excitability 4, 7, 12, 17, 42 and decreased FS cell firing 3 without significant increases in pyramidal cell activity. Additionally, peritumoral FS cell firing was less likely to be interictal, as it occurred predominantly within epileptiform bursts.…”
Section: Discussionsupporting
confidence: 92%
“…Features of this core-penumbra organisation of epileptic activity have previously been described both in human microelectrode recordings in chronic epilepsy, and in vitro using optical imaging of acutely induced seizures in cortical slices, where these dynamics unfold across temporal and spatial scales comparable to the ones reported here 7 . Similar to previous reports 7, 37 , individual ictal discharges may spread near-synchronously across the whole µECoG recording array, while calcium fluorescence, and to some extent signal amplitude on the µECoG array, expands slowly across the recorded surface. We treat this slow spatial evolution of the seizure as a traveling wave phenomenon 9 , where we consider the boundary between significantly increased calcium fluorescence and activity nearer the resting state background level to be the edge of the ictal core ( Fig.…”
Section: Calcium Imaging Shows Slow Spatial Evolution Of the Ictal Coresupporting
confidence: 86%
“…Seizure-like burst firing recorded in CPNs at single-cell levels may suggest a larger network of synchronized neuronal activities. To test this possibility, we performed extracellular multi-electrode array recording in brain slices from CTRL and CKO mice after postnatal week 8, as in Gill et al (2020) . Raw extracellular signals were digitally filtered to extract local field potentials (LFPs) and multiunit activity (MUA), and neuronal firing was quantified across cortical depth.…”
Section: Resultsmentioning
confidence: 99%
“…Multi-electrode array (MEA) recording was conducted as described in Gill et al, 2020 . Acute brain slices were placed on top of a 4X4 mm MEA system with 96 electrodes (10x10 grid, Blackrock Microsystems, Inc., USA), recorded for 10 min in ACSF containing 5 mM KCl and 2 mM CaCl 2 , followed by 30 min in Mg 2+ free ACSF solution at a flow rate of 6 mL/min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation